Analisis Atribut Produk Terhadap Kepuasan Pelanggan Pada Ranu Original Store Jakarta Selatan - Annida Zahra; Anah Furyanah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Ranu Original Store specializes in authentic fashion and sneakers. It operates as a digital provider for school procurement, focusing on education-related products, rather than clothing or general retail goods as the name